The American sonnet : an anthology of poems and essays - Malech, Dora; Smith, Laura T., 1975- (University of Iowa Press, 2022)
"The American Sonnet: An Anthology of Poems and Essays showcases the diversity of the American sonnet. 800 years after the sonnet's invention, this volume celebrates the extraordinary development of the sonnet in the hands of American poets-and those living under US empire-from traditional to experimental, political and personal. Edited by poet and scholar team Dora Malech and Laura T. Smith, this anthology collects and foregrounds an impressive range of 20th and 21st century sonnets, including formal and formally subversive sonnets by established and emerging poets, and presents these alongside a selection of earlier American sonnets, highlighting connections across literary moments and movements. The critical essays likewise draw together diverse voices, methodologies, and historical and theoretical perspectives that represent the burgeoning field of American sonnet studies. Malech and Smith capture the central questions for American sonneteers. Who belongs to the tradition of the American sonnet? How do translation and multicultural and transnational identities complicate the Americanness of the "American" sonnet? How do Black, queer, trans, neurodiverse, working class, Appalachian, and Deaf poets claim the sonnet and how does it serve them? How do American poets experiment with meter, stanza, rhyme, lineation, and visuality to make the sonnet their own? And how are American sonneteers writing about love, loss, and trauma in new ways that change the sonnet tradition? The American Sonnet shows the form continuing to function as a poetic bellwether as centuries of poets use its peculiar confines to negotiate questions of nation, race, class, gender, sexuality, diaspora, and poetic tradition"--